Investigating the Effect of Consumer Ethnocentrism, Cosmopolitanism, and Relative Product Quality to Brand Preferences: An Insight from Generation Z in Indonesia - Eva Yunitasari; Cesya Rizkika Parahiyanti (Bina Nusantara University, 2022)
The development of the economy in the current globalization era is increasingly rapid. The business world in various industries has tight competition, including the makeup industry. The research aimed to explore Generation Z’s preferences toward global brand makeup products in Indonesia. It applied a quantitative research with descriptive analysis. The data using a questionnaire distributed to 236 respondents were calculated using Partial Least Square (PLS). The results find that cosmopolitanism does not directly contribute to Generation Z’s preferences for global makeup products in Indonesia or through relative product quality. Meanwhile, consumer ethnocentrism has a positive influence on Generation Z's preferences for global makeup products in Indonesia directly or through relative product quality. It also shows that the relative product quality of global makeup products in Indonesia positively affects Generation Z’s preferences. The research findings provide insights for local makeup producers to improve their quality and compete more with global makeup products. Generation Z, as makeup consumers in Indonesia, prefers to purchase products based on quality. Buying global brand makeup products does not make them lose the spirit of nationalism towards their country. However, the research is only limited only to Generation Z as the samples in Indonesia. Therefore, there is an opportunity for different results if the research is carried out in other regions or with consumers from other generations.